The application of blockchain technologies in information security and computer systems data - Shevchuk, Yurii; Tytarchuk, Yevhenii; Zybin, Serhii; Sorokun, Anton; Khometa, Taras (Sustainable Engineering and Innovation, 2026)
The rapid expansion of digital systems and the increasing frequency of cyberattacks have made information and data security a critical global concern. This challenge is particularly severe in Ukraine, where prolonged conflict with Russia has involved hybrid warfare, including persistent cyberattacks on digital and information infrastructures. This study examines the use of blockchain technology to improve secure data management through an intelligent Hybrid Blockchain–Relational (HBR) architecture. Sensitive data are stored on a private blockchain (Hyperledger Fabric), while less sensitive data are maintained in a relational database (PostgreSQL), with data integrity ensured through Merkle root anchoring. A simulation using Ukraine’s Land Cadaster data served as the case study. Under Byzantine fault and system degradation conditions, Blockchain-based Consensus Optimization (BRCO) achieved a 40% reduction in transaction completion time and a 66.7% increase in node fault tolerance compared to Practical Byzantine Fault Tolerance (PBFT). The proposed HBR+BRCO design demonstrated low latency (50 ms), efficient resource usage, and a throughput of 500 TPS, highlighting its effectiveness and real-world applicability.